O ensino de História, memória e história local : um estudo do município de Rolim de Moura-RO - Ferreira, Gabriel Filipe Cassol Cortez (2020)
The state of Rondônia is one of the youngest states in Brazil in terms of its emancipation. Because it was colonized by migrants who came from other regions and given its history being considered recent, sometimes its own population does not value it. This situation has a direct impact on the teaching of History of Rondônia, which through a law is part of the curriculum of regular high schools. Until recently, the discipline's teaching had its rigor raised in the fact that the Federal University of Rondônia demanded it as a requirement in the selection process. Today, local and regional teaching, besides showing little interest on the part of the students and sometimes laborious for teachers, has no basis for learning the history of the municipalities themselves, especially those in the interior. With these assumptions in mind, the present work seeks to problematize the teaching of local and regional history of the municipality of Rolim de Moura with the proposal of creating a didactic material elaborated from interviews with oral sources delimited on the daily history of the municipality throughout the 1980s. The material would be indicated for work with students still in elementary school and would start from the idea of approaching and valuing the local, demonstrating the changes that the municipality has been going through.